Contemporary topics in deep foundations : proceedings of selected papers of the 2009 International Foundation Congress and Equipment Expo, March 15-19, 2009, Orlando, Florida - Iskander, Magued; Laefer, Debra F.; Hussein, Mohamad H. (Geotechnical special publication ;, 2009)
These papers on deep foundations, ground support and earth retention were presented at the 2009 International Foundation Congress and Equipment Expo to give geotechnical professors, students and engineers a survey of the latest research and technological advances. The editors have included research articles and case studies on drilled shaft applications, the use of driven piles and micropiles, continuous flight auger (CFA) piles, helical piles and anchors, wind energy converter foundations and foundation testing. Two companion volumes address testing and analysis of foundations as well as ground foundations and geo- support. --